Comparison of the effects of post-spinning drawing and wet stretching on regenerated silk fibers produced through straining flow spinning. (15th August 2018) - Madurga, Rodrigo; Gañán-Calvo, Alfonso M.; Plaza, Gustavo R.; Atienza, José Miguel; Guinea, Gustavo V.; Elices, Manuel; López, Patricia A.; Daza, Rafael; González-Nieto, Daniel; Pérez-Rigueiro, José
Abstract: Straining Flow Spinning is a versatile and robust spinning technique for the production of regenerated silkworm silk fibers using mild chemistries. However, reaching high values of tensile strength and strain at breaking requires a step of wet-stretching in water, which limits scalability and the practical usage of the technique. Here, we show that adding a post-spinning drawing step to the procedure improves the performance of the fibers, and allows the development of a scalable process. It is also shown that the properties of the fiber can be tuned by varying the parameters of the post-spinning step. Finally, equivalence is established between the discrete wet-stretching process and the continuous post-spinning drawing step. Graphical abstract: Image 1 Highlights: Addition of a post-spinning drawing step leads to SFS high performance fibers The effect of post spinning drawing is summarized in the alignment parameter, α Continuous production of high performance fibers allows developing novel applications